Application of Project Based Learning (PjBL) Assisted by Google My Maps on Students' Spatial Thinking Ability in Geography Learning Material Distribution of Natural Resources - Agus Supriyanto (UM Purwokerto Press, 2025)
This study aims to determine the effect of the application of Project Based Learning (PjBL) learning model assisted by Google My Maps digital media on students' spatial thinking skills in learning geography on natural resource distribution material. The method used was quasi-experiment with post-test only control group design, involving two XI classes at SMAN 1 Jeruklegi, namely experimental class (using PjBL and Google My Maps) and control class (using conventional learning). Data were collected through multiple choice and essay tests that have been adjusted to the indicators of spatial thinking ability. The results showed that the average post-test score of the experimental group was higher (81.38) than the control group (73.33), with the majority of students in the experimental group in the